1997
DOI: 10.1152/jappl.1997.82.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute hyperoxic exposure on solute fluxes across the blood-gas barrier in rat lungs

Abstract: Zheng, Lu P., Rui Sheng Du, and Barbara E. Goodman.Effects of acute hyperoxic exposure on solute fluxes across the blood-gas barrier in rat lungs. J. Appl. Physiol. 82(1): 240–247, 1997.—We investigated effects of acute hyperoxia on solute transport from air space to vascular space in isolated rat lungs. Air spaces were filled with Krebs-Ringer bicarbonate solution containing fluorescein isothiocyanate-labeled dextran (FD-20; mol wt 20,000) and either22Na+and [14C]sucrose, ord-[14C]glucose andl-[3H]glucose. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The first finding was that basal alveolar fluid clearance did not change for 56 h. Similar results were observed in the studies where basal alveolar fluid clearance was sustained (6,21); and terbutaline, a selective b2-adrenergic agonist, increased alveolar fluid clearance in rats exposed to >95% oxygen for 40 and 60 h (6,7). In contrast to this study, rats exposed to 100% oxygen for 60 or 64 h had a decreased basal rate in alveolar fluid clearance, active sodium transport and Na + -K + ATPase activity (20,22).…”
Section: Discussionsupporting
confidence: 80%
“…The first finding was that basal alveolar fluid clearance did not change for 56 h. Similar results were observed in the studies where basal alveolar fluid clearance was sustained (6,21); and terbutaline, a selective b2-adrenergic agonist, increased alveolar fluid clearance in rats exposed to >95% oxygen for 40 and 60 h (6,7). In contrast to this study, rats exposed to 100% oxygen for 60 or 64 h had a decreased basal rate in alveolar fluid clearance, active sodium transport and Na + -K + ATPase activity (20,22).…”
Section: Discussionsupporting
confidence: 80%
“…We have confirmed that hyperoxia causes pulmonary edema in adult rats, as corroborated by the presence of pleural fluid in the thoracic cavity (volume: 9.1 Ϯ 0.6 ml) and a three-to fourfold increase in the alveolar ELF volume after 64 h of exposure to 100% O 2 . The lung permeability to small solutes (Na ϩ , mannitol) and large solutes (albumin) significantly increased after hyperoxia-induced lung injury, probably because of damage of lung capillaries (9,23,25,33,35). The different results that were obtained with the EBD-albumin and FITC-albumin assay probably represent a higher sensi- Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Abernathy et al (1) have used radiolabeled dextran compared with albumin to evaluate macromolecule transport across the alveolar capillary membrane; however, their goal was not to measure a leak. Zheng et al (33) investigated effects of acute hyperoxia on solute transport in isolated rat lung by filling air spaces with solutions containing FITCdextran and other markers. However, to our knowledge, FITC-dextran has not yet been measured in the BAL to evaluate lung epithelial injury.…”
Section: Discussionmentioning
confidence: 99%